Performance evaluation of physical layer using LoRa technology for indoor environment - Ismail, I. S. (International Journal of Scientific and Technology Research, 2020)
Low Power Wide Area Network is a new wireless technology which is designed for low power with long-range communication, and LoRa is one of the primary solutions of the technology. The objective of this paper is to evaluate the performance of the physical layer of LoRa Technology in an indoor environment. An experimental testbed is conducted using LoRa module as LoRa transmitter and receiver node and several LoRa parameters such as transmit power, bandwidth, spreading factor and coding rate are exploited. A series of experiments are performed at different locations with different LoRa parameters to investigate the effect of these parameters on the packet data throughput, received signal strength indication and signal-to-noise ratio. The results showed that the combination of different LoRa physical parameters have a clear impact on the overall performance. In addition, the external parameters such as the variant of distance between the transmitter and the receiver node and the obstacles that exist between the two nodes can also affect the performance of LoRa network.